Administration Status of Vocational Education - สมจิตฺโต พระครูปฐมเจติยานุรักษ์; นันทเพ็ชร กฤษฎา (Journal of Educational Review Faculty of Education in MCU, 2018)
Administrators, teachers and the school board should be trained to develop themselves with knowledge, the role in education management and the participation in educational management to be able to express opinions and to work with school personnel effectively. Although lack of skills and knowledge but the administrators can develop themselves to work in academic field, education management with students’ parent network and to cooperate between schools and communities in providing education to students, advantages to school and community and students’ parents.